ADVENTURE FORMULA STORYLINE IN MAD MAX: FURY ROAD (2015) MOVIE DIRECTED BY GEORGE MILLER - Nuraini, Sri; Sudarisman, Yoga; Hkikmat, Mahi M (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2024)
This research attempts to examine the adventure aspect that focuses on the storyline in the popular movie